Persepsi Guru Terhadap Pelaksanaan Supervisi Pendidikan dan Perannya dalam Peningkatan Mutu Pendidikan di SMA Negeri 1 - Diannita, Artika (Jurnal Studi Islam dan Sosial, 2022)
This study aims to 1) know the role of the principal in the implementation of supervision at SMA Negeri 1 Ngawen; 2) knowing the efforts of the school principal in ensuring the effectiveness of the supervision program; 3) determine the implementation of supervision at SMA Negeri 1 Ngawen; 4) know the purpose of implementing Supervision at SMA Negeri 1 Ngawen;and 5) knowing the perceptions of SMAN 1 Ngawen’s Teachers on the implementation of supervision at SMAN 1 Ngawen’s. The research was conducted at SMA Negeri 1 Ngawen. This study uses a quantitative approach, and this study uses a descriptive qualitative research design. The population in this study were all teaching and academic staff at SMA Negeri 1 Ngawen. The sample ofthis research is the headmaster and teachers of SMA Negeri 1 Ngawen with a total of 50 people. The research sample was determined using purposive sampling and snowball sampling techniques. Data was collected by using interviews, observation, and documentation. The data analysis technique used in this research is the qualitative data analysis technique. Qualitative research data is obtained continuously (triangulation) and is carried out always. The research results show that; 1) the implementation of the supervision program at SMAN 1 Ngawen, preceded by the monitoring process and then continued with the implementation of supervision after the supervision was carried out, an evaluation and follow-up process was carried out, 2) the Supervision program at SMAN 1 Ngawen aimed at monitoring/supervising, coaching and improving the learning process, 3) the principal of SMAN 1 Ngawen plays a vital role in supervision activities, 4) SMAN 1 Ngawen teachers' perceptions of supervision, namely having at least three views, namely supervision as an assessment tool, supervision as a coaching tool and supervision as areflection tool